Improving coaches and parents' knowledge and attitude towards sport sciences implementation: a community-based program in football schools (SSB) in Sleman - Muslichah, Rahadyana; Ermamilia, Aviria; Penggalih, Mirza; Prabandari, Yayi; Sabirin, Rahmaningsih; Wibowo, Rakhmat; Niamilah, Ibtidau; Reswati, Vigur; Utari, Diajeng; Fadilah, Lailatul; Khumairoh, Rahmatika (Journal of Community Empowerment for Health, 2024)
Introduction: Many young athletes joined football schools (SSB) to gain and improve their skills, aiming to participate further in high-level competitions. However, most SSB management lacked comprehension of sports sciences, essential to support young athletes' growth and development and improved sports performance. This program aimed to improve coaches' and parents' knowledge and attitudes towards sports sciences and its implementation in SSB. Methods: Involving representatives from 13 SSBs in Sleman, an integrated training on sports sciences comprising of long-term athlete development (LTAD), nutrition and psychological development for young athletes, coaching program, and management of SSB was carried out. Knowledge was measured before and after training using questionnaires consisting of multiple-choice questions (MCQ). A focus group discussion (FGD) was also conducted to assess participants' knowledge and attitudes about implementing sports sciences in SSB. Changes in knowledge scores were analyzed using the Wilcoxon Signed Rank Test. Results: Thirty-five participants completed both pre-test and post-test, whereas only 17 participated in the FGD. The mean score during the post-test increased significantly by 12.71 points compared to the pre-test (74.29 vs. 61.58, p<0.05) with increased passing rate (57.14% vs 25.71%). Individual's change in knowledge improved by 28.83%. As stated during FGD, participants believed in the benefits of implementing sports sciences on athletes' growth and development, health, well-being, and performance. They also believed in the possibility of implementation, considering the growing number of licensed coaches. However, the inhibiting factors might be a lack of capable human resources, funding, readiness, and knowledge. Fortunately, a few SSBs reported having partially implemented sports sciences, and all SSBs are willing to start implementing sports sciences by educating all involved parties regarding sports sciences. Conclusion: These findings concluded the program's success and the promising possibility of sports sciences implementation in SSB.